Keys of the pacific rise of china and the failed parallel in latin america (2009)
Most contemporary China-reform process analysts ignore the critical reliance of such process on the long and (perhaps) unsuccessful history of capitalist global economic expansion into the Far East, a history that includes the clash and fusion of capitalistic production methods with Asiatic innovations such as the invention of an international nation-state system operating independently from the model of Westphalian balance of power; or, the development of a technological revolution (industrous revolution) in China, different from the European industrial revolution, with a major impact on world GNP. In addition, world-systems school analysts, although more sensitive to the influences of long-term processes on current reforms, have failed to note a curious asymmetric parallel between contemporary Chinese reforms and the history of both American philosophical pragmatism and its Marxist association, and, the vicissitudes of a Latin American movement, specially associated with the Golconda Group, in its bitter search for an authentic development model. This paper attempts to chronicle the existence of such unexplored connections.